Performance analysis of free space optical communications employing Duty Cycle Division Multiplexing - Khazaali, Maryam (2015)
Expanding request for more new broadband services everywhere, caused an explosive capacity growth in communication networks during past few years. Fiber optics is an enabler to provide high speed communications. However, in regions where fiber is not employable, Free Space Optics (FSO) system is proposed as one effective solution for last mile bottleneck. FSO is a wireless optical network which transmits high data rates by narrow laser beam between a pair of communicating transceivers through the air. Despite the fact that FSO is license free, cheap to implement, fast to install, and extremely directional with abundant bandwidth, the atmospheric factors have vigorous impact on its performance. FSO link range is highly limited by atmospheric attenuation. In this study, the effect of atmospheric attenuation such as turbulence, scattering, absorption, scintillation and spreading in different weather conditions is investigated based on gamma-gamma distribution with On-Off keying (OOK). Multiplexing is a technique where multiple data streams are transmitted simultaneously through a single link to increase the transmission capacity and reduce the system costs. The main contribution of this research can be considered as employment of Duty Cycle Division Multiplexing (DCDM) in FSO to transmit data for different users on the same laser beam. This way, more number of users are accommodated using less number of lasers which is more economical and cost effective. As a first step, DCDM architecture is designed for both single channel and multi-channel transmission. System performance is investigated analytically based on the design metrics such as optical received power, optical signal to noise ratio (OSNR), bit error rate (BER) and link range. Results show that adverse weather conditions confine the supported FSO link range dramatically, as much higher transmitter power is needed to cover a mile of distance under heavy Malaysian rain. Although using proposed DCDM to send multiple users on a single laser slightly reduces the link range, it also introduces several advantages such as: higher optical received power efficiency, less number of required components and cost effective. Furthermore, two different design of proposed DCDM obtain significantly smaller OSNR (1.9 dB and 3.3 dB), and higher energy saving (18.78% and 31.63%) compared to conventional WDM.